Fluorine-free transparent self-cleaning solid lubricating coating and preparation method thereof

Fluorine-free transparent self-cleaning solid lubricating coating prepared by wax-based suspension solves the contradiction between high transparency and self-cleaning performance of traditional coatings, achieving environmentally friendly, low-cost and efficient coating applications.

CN119823644AActive Publication Date: 2025-04-15JIANGSU UNIV

Patent Information

Application Number
CN202510051960.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-15
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

The prior art is difficult to provide self-cleaning and anti-fouling properties for solar photovoltaic panels while ensuring high transparency, and the traditional superhydrophobic coating uses fluorine-containing substances and a large number of organic reagents, resulting in environmental protection and cost problems.

Method used

A fluorine-free transparent self-cleaning solid lubricating coating is prepared using a wax-based suspension. Through the combination of wax powder, a hydrophobic binder and a hydrophilic nanosilica, a coating with good hydrophobicity and transparency is formed, and silanes and fluorinating agents are avoided.

Benefits of technology

It achieves high transparency, excellent self-cleaning, hydrophobicity and durability. It is simple and environmentally friendly in preparation, and has no fluorine-free VOC emissions. It is suitable for solar panels, building exterior walls and automotive surfaces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823644A_ABST
    Figure CN119823644A_ABST
Patent Text Reader

Abstract

The invention relates to a fluorine-free transparent self-cleaning solid lubricating coating and a preparation method thereof.The solid lubricating coating is formed by coating a substrate with wax-based suspension liquid and curing the wax-based suspension liquid, the wax-based suspension liquid is prepared by dispersing wax micro-powder, a hydrophobic adhesive and hydrophilic nano-silicon dioxide in a solvent, the wax micro-powder provides roughness and hydrophobicity, and the hydrophobic adhesive and the hydrophilic nano-silicon dioxide are dispersed in the solvent; the hardness of the coating and a certain water contact angle are increased by hydrophilic nano silicon dioxide, so that the coating has good optical transparency, excellent self-cleaning performance, hydrophobicity, stability and durability, preferably, the transparency can reach 99%, the hydrophobic performance can still be kept after abrasive paper abrasion, gauze abrasion, sand impact, water impact and acid rain impact, and the service life of the coating is prolonged. Meanwhile, the preparation method is simple and environment-friendly, fluorine and VOC emission is avoided, the addition amount of the wax is not limited by preparation, the wax can be flexibly adjusted, the wax can be suitable for multiple fields such as solar panels, building outer walls and automobile surfaces, the power loss of the photovoltaic panel subjected to self-cleaning preferably can be smaller than or equal to 1%, and wide commercialized application prospects are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coating materials, and in particular relates to a fluorine-free transparent self-cleaning solid lubricating coating and a preparation method thereof. Background Art

[0002] Solar photovoltaic power generation is known for its inexhaustible, continuous, low-carbon and high-efficiency advantages. In order to achieve net zero emissions using renewable energy, solar photovoltaic power generation is expected to become a key part of building a new power system. However, in actual applications, solar photovoltaic panels are seriously polluted every year, especially in some areas with frequent sandstorms and strong winds. The accumulated dust in one month will cause the efficiency of solar photovoltaic panels to drop by 18.74%, seriously affecting the performance of photovoltaic components, reducing the photoelectric conversion efficiency and affecting the power generation benefits. Therefore, researchers are looking for a special functional surface with self-cleaning and high transparency to ensure the power generation capacity of solar photovoltaic panels, reduce the pollution of photovoltaic panels and reduce maintenance costs.

[0003] In the prior art, researchers were inspired by the water-repellent properties of the lotus surface, and designed a bionic functional surface by imitating the microstructure of the lotus surface and using low surface energy materials, namely a super-hydrophobic surface. This surface has the advantages of anti-fouling, anti-corrosion, anti-icing, anti-ultraviolet, anti-bacterial, flame retardant, etc. For example, patent CN118994688A discloses a method for preparing a super-hydrophobic self-cleaning layer, a flexible protective component and a preparation method thereof, and a self-cleaning coating designed by combining a micro-nano hierarchical structure with a fluorinated silane-perfluoropolyether mixture. However, on the one hand, the micro-nano structure required for the super-hydrophobic surface is different from the light transmittance required for the photovoltaic panel. The contradiction between the two limits the application of super-hydrophobic coatings in photovoltaic cells. Therefore, how to give the surface anti-fouling properties while ensuring high transparency is an urgent problem to be solved. On the other hand, in order to achieve the hydrophobic and lubricating properties of most super-hydrophobic / hydrophobic coatings, fluorine-containing substances are required to modify the coatings, and a large amount of organic reagents are used in the preparation process, which not only increases the cost but also causes harm to the environment. A large amount of VOC emissions is not conducive to large-scale industrial production. In order to meet the requirements of sustainable development, it is urgent to explore a more environmentally friendly preparation process without fluorine and VOC emissions to reduce the negative impact on human body and environment.

[0004] In order to improve the hydrophobicity of the coating surface, hydrophobic silica is also introduced into the coating surface in the prior art. For example, the SiO2 / PVDF hydrophobic self-cleaning coating solution and its preparation method and application disclosed in patent CN118755322A uses OTS to modify nano-SiO2, and introduces PVDF to prepare PVDF@OTS-SiO2 coating suspension, which is sprayed to form a transparent hydrophobic coating. Although hydrophobic silica has a good hydrophobic effect, silane or fluorinating agent is used to make silica achieve the hydrophobic effect. On the one hand, the preparation process is complicated and cumbersome, and the production cost is high. On the other hand, silane and fluorinating agent will also cause harm to the environment, which will limit their commercial application. Summary of the invention

[0005] The present invention aims to solve at least one of the above-mentioned technical problems to a certain extent. The present invention provides a fluorine-free transparent self-cleaning solid lubricating coating and a preparation method thereof. The coating has good optical transparency, excellent self-cleaning, hydrophobicity, stability and durability. The preparation method is simple and environmentally friendly, and it is fluorine-free and VOC-free, so that it can be used in multiple fields such as solar panels, building exterior walls, and automobile surfaces, and has broad commercial application prospects.

[0006] The technical solution adopted by the present invention to solve its technical problem is:

[0007] A fluorine-free transparent self-cleaning solid lubricating coating is formed by coating a wax-based suspension on a substrate and solidifying the wax-based suspension, wherein the wax-based suspension is prepared by dispersing wax micropowder, a hydrophobic adhesive and hydrophilic nano-silicon dioxide in a solvent.

[0008] The transparent self-cleaning lubrication mechanism of the above solid lubricating coating includes:

[0009] The hydrophobic adhesive not only plays the role of bonding the substrate, but also provides the hydrophobicity of the coating, thereby enhancing the moisture resistance and anti-fouling properties of the coating. The addition of hydrophilic nano-silica not only improves the hardness of the coating, but also enhances the structural stability of the coating through its strong inorganic properties. In the initial state of the coating, the hydrophilic nano-silica and wax micropowder, which are mainly in the shape of micrometer-sized spheres, are evenly dispersed in the coating. No modification with silane and fluorinating agent is required, and a rough surface structure can be formed. This rough structure is covered by the hydrophobic adhesive, forming surface protrusions covered by the hydrophobic adhesive. These surface protrusions provide a relatively rough surface, and the surface energy of the initial coating is not significantly reduced.

[0010] As the coating is heated to the softening or melting temperature of the wax powder, the wax powder begins to soften or melt and spread on the surface, producing an additional lubricating effect. At this time, the softening or melting of the microcrystalline wax not only fills the microscopic gaps on the coating surface, but also reduces the local high surface energy areas on the surface, thereby reducing the surface energy of the coating as a whole. At the same time, as the wax powder softens or melts, the surface roughness of the coating is further optimized, so that the solid lubricating coating forms a smoother and more transparent coating structure, improving the overall hydrophobic lubrication properties, so that dust, rainwater, etc. that are much larger than the surface protrusions can form a spherical shape and slide out of the coating surface under the action of surface tension when they fall on the coating surface, thereby giving the coating surface anti-fouling properties and achieving a transparent self-cleaning hydrophobic lubrication effect.

[0011] In a preferred embodiment, the particle size of the wax powder is 5 to 20 μm. The wax powder can be directly added to the solvent without heating and melting the wax, and can be evenly dispersed by stirring at room temperature, which is beneficial to reducing energy consumption and further improving the simplicity of preparation.

[0012] The wax powder is used to provide a certain roughness and hydrophobicity to the coating, but the wax powder is in the form of white powder. To further avoid excessive wax powder and loss of optical transparency of the coating, in a preferred embodiment, the weight concentration of the wax powder in the solvent is 0.3wt% to 2wt%. Taking into account the hydrophobicity and transparency of the coating, it may be further preferably 0.6wt% to 1wt%.

[0013] In a preferred embodiment, the hydrophobic adhesive is PDMS. Polydimethylsiloxane is a high molecular weight organic silicon compound that can provide a certain hydrophobicity and also acts as an adhesive in the coating, allowing a stable interfacial active system to be formed between the wax micropowder and the hydrophilic nano-silica. In addition, PDMS itself has high transparency and will not affect the transparency of the coating.

[0014] In order to take into account the hydrophobicity and adhesive effect of PDMS and further avoid excessive PDMS that is detrimental to smooth spraying, in a preferred embodiment, the weight concentration of the PDMS in the solvent is 5wt% to 40wt%. Considering the hydrophobicity and transparency of the coating, it can be further preferably 20wt% to 30wt%.

[0015] In order to take into account the role of hydrophilic nano-silica in increasing the hardness of the coating and a certain water contact angle, and further avoid excessive hydrophilic nano-silica and loss of coating hydrophobicity and optical transparency, in a preferred embodiment, the weight concentration of the hydrophilic nano-silica in the solvent is 0.3wt% to 1wt%. Taking into account the hydrophobicity and transparency of the coating, it can be further preferably 0.5wt% to 0.7wt%.

[0016] In a preferred embodiment, the particle size of the hydrophilic nano-silica is ≤20 nm, and in order to further control material cost, it may be further preferably 10 to 20 nm.

[0017] In a preferred embodiment, the solvent is an ethyl acetate solution, which has good solubility for PDMS.

[0018] A method for preparing a fluorine-free transparent self-cleaning solid lubricating coating, the preparation method comprising:

[0019] Preparation of wax-based suspension: adding wax micropowder to a solvent, and then adding a hydrophobic adhesive and hydrophilic nano-silica to disperse uniformly to prepare a wax-based suspension;

[0020] Preparation of self-cleaning lubricating coating: spraying the wax-based suspension onto the surface of a substrate and curing the wax-based suspension to obtain a self-cleaning lubricating coating.

[0021] In the above preparation method, wax micropowder is used as an additive and directly added to the solvent, which can avoid the step of heating and melting the wax, can be evenly dispersed at room temperature, reduce energy consumption, and improve ease of operation. At the same time, a wax-based suspension is prepared with a hydrophobic adhesive and hydrophilic nano-silica, which solves the dispersion problem of traditional wax particles in the solution, and can avoid the problem of wax precipitation and spray gun clogging caused by the rapid drop in solution temperature during spraying after the wax is melted, thereby ensuring the smooth progress of the spraying process, so that the addition amount is no longer limited and can be flexibly adjusted, which is conducive to improving the stability and operability of the preparation method.

[0022] In order to quickly obtain wax micropowder with uniform and fine particle size, in a preferred embodiment, the preparation method thereof includes:

[0023] Preparation of wax micropowder: Heat and dissolve the microcrystalline wax, spray it out through a spray gun, and collect it to form spherical wax micropowder.

[0024] In a preferred embodiment, when preparing wax micropowder, water bath heating is used to dissolve the microcrystalline wax, which can improve the dissolution uniformity and stability.

[0025] In a preferred embodiment, magnetic stirring and ultrasonic dispersion are used when preparing the wax-based suspension, and ultrasonic dispersion can be used to further improve the uniformity of the wax-based suspension and improve the processing efficiency.

[0026] In a preferred embodiment, when preparing the self-cleaning lubricating coating, anhydrous ethanol is used to clean the substrate surface before spraying, so as to prevent the substrate from being contaminated and affecting the coating preparation or interfering with the coating performance.

[0027] In a preferred embodiment, when preparing the self-cleaning lubricating coating, the wax-based suspension is sprayed at a distance of 10 to 15 cm from the substrate and perpendicular to the substrate at an air pressure of 0.2 to 0.5 MPa to form a uniform coating.

[0028] In a preferred embodiment, when preparing the self-cleaning lubricating coating, air-blast drying and curing at 60-80° C. are used to improve the curing efficiency.

[0029] The application of the above-mentioned fluorine-free transparent self-cleaning solid lubricating coating includes using the solid lubricating coating on solar panels, building exterior walls, and automobile surfaces.

[0030] Compared with the prior art, the beneficial effects of the present invention are at least:

[0031] (1) The solid lubricating coating of the present invention uses wax micropowder to provide a certain degree of roughness and hydrophobicity, and uses a hydrophobic adhesive to enhance the hydrophobicity and act as an adhesive, so that the hydrophilic nano-silica can adhere to the surface of the wax micropowder, increase the hardness of the coating and a certain water contact angle, so that the coating has excellent hydrophobicity and stability, and can still maintain hydrophobic properties after sandpaper wear, gauze wear, sand impact, water impact and acid water impact. At the same time, the coating has good optical transparency. According to tests, the transparency can reach >90%, preferably up to 99%, which solves the problem in the prior art that it is difficult to take into account both high transparency and self-cleaning and anti-fouling properties of the coating.

[0032] (2) The solid lubricating coating of the present invention does not need to be modified with silane and fluorinating agent, and can be prepared using a fluorine-free method, which has no fluorine and no VOC emissions, making the preparation simple and environmentally friendly, which is conducive to reducing production costs and has a wider commercial application prospect.

[0033] (3) The present invention adopts wax micropowder directly added into the solvent, which can be evenly dispersed at room temperature, thereby effectively reducing energy consumption and improving the simplicity of operation. At the same time, by preparing a wax-based suspension with a hydrophobic adhesive, hydrophilic nano-silica and a solvent, the dispersion problem of traditional wax particles in the solution is solved, and the problem of wax precipitation and spray gun clogging due to the rapid drop in temperature during spraying can be avoided, further ensuring the smooth progress of the spraying process. At the same time, the amount of wax added is no longer limited and can be flexibly adjusted, further improving the stability and operability of the preparation method, which is conducive to expanding its application field.

[0034] (4) The solid lubricating coating of the present invention is applied to the surface of solar panels, which can effectively reduce the impact of pollution on the efficiency of solar panels and provide protection for photoelectric conversion, thereby improving the efficiency of solar panels and extending their service life, and reducing the power loss after self-cleaning after pollution. According to tests, the loss can reach ≤13%, preferably ≤1%. Its excellent self-cleaning, hydrophobicity and durability lay the foundation for achieving wider commercial applications, making it also suitable for multiple fields such as building exterior walls and automobile surfaces. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0036] Figure 1 is a SEM image of the wax powder obtained in step S1 of Example 1 of the present invention;

[0037] Figure 2 is a water contact angle WCA graph of the solid lubricating coating obtained in Example 8 of the present invention;

[0038] Figure 3 This is a transparency test effect diagram of the solid lubricating coating obtained in Example 8 of the present invention;

[0039] Figure 4 This is a transparency test result diagram of the solid lubricating coating obtained in Example 8 of the present invention at different wavelengths;

[0040] Figure 5 is a data graph of the hydrophobic performance of the solid lubricating coating obtained in Example 8 of the present invention after being abraded by sandpaper;

[0041] Figure 6 This is a data graph of the hydrophobic performance of the solid lubricating coating obtained in Example 8 of the present invention after being rubbed with gauze. DETAILED DESCRIPTION

[0042] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0043] In the following examples and comparative examples, the sources of reagents and testing equipment used include:

[0044] Microcrystalline wax (melting point 67-72°C) was purchased from Shanghai Yuanye Biotechnology Co., Ltd.; Dow Corning 184PDMS was purchased from Suzhou Hongyuanda E-commerce Co., Ltd.; hydrophilic nano-silicon dioxide particles (particle size 10-20 nm) and anhydrous ethanol were purchased from Sinopharm Chemical Reagent Co., Ltd.; solar photovoltaic panels (parameters of 1W, 5V, 200mA) were purchased from Dongguan Liaobu Huixu Trading Co., Ltd.; spray gun Gunze PS289 (caliber 0.3mm) was purchased from Ji'an Ruyi Model E-commerce Co., Ltd.; Shengli VC86E multimeter was purchased from from Xi'an Beicheng Electronics Co., Ltd.; the light meter (split type TA630B) was purchased from Suzhou Zoff Electronics Co., Ltd.; the DuPont line was purchased from Shenzhen Chickpea Technology Co., Ltd.; the solder wire was purchased from Shenzhen Nantian Electronics Co., Ltd.; the glass slide, sandpaper, and flannel were purchased from Henan Anning E-Commerce Co., Ltd.; the weights were purchased from Shanghai Yanheng Instrument Co., Ltd.; the mud powder was ground from the mud on campus, and the water was deionized water from the laboratory; the commercial coating, the main component of which is epoxy resin, has high transparency, about 99%, and is used on a large scale in the photovoltaic field, and was purchased from Taobao.

[0045] In the following embodiments and comparative examples, the test method of the coating includes:

[0046] (1) Test the hydrophobicity of the solid lubricating coating of the sample: Use the OCA20 contact angle tester to test the hydrophobicity of the surface of the solid transparent lubricating coating to obtain the water contact angle WCA and the rolling angle WSA.

[0047] (2) Optical transparency of the solid lubricant coating of the test sample: The optical transparency of the coating was tested using a Shimadzu UV2600 ultraviolet-visible spectrophotometer.

[0048] (3) The power loss of the solid lubricating coating and the commercial coating after self-cleaning under the same pollution environment was tested: the power loss of the photovoltaic panel after self-cleaning was controlled to be about 68% to 75% under the conditions of controlling the water volume used for self-cleaning to 15 mL and the dust density to cause the power loss of the photovoltaic panel after pollution to be about 68% to 75%. The power loss of the two after self-cleaning was tested using a multimeter under the conditions of controlling the light intensity to be constant at 26900 lx. The power loss after self-cleaning (%) was used to represent the power loss of the photovoltaic panel with the solid lubricating coating after self-cleaning, and the power loss after self-cleaning (%) of the photovoltaic panel with the commercial coating was used to represent the power loss of the photovoltaic panel with the commercial coating after self-cleaning.

[0049] (4) Test the hydrophobicity of the solid lubricating coating of the sample after sandpaper friction: The solid lubricating coating of the sample was rubbed 30 times with 1000-grit sandpaper under a 50 g weight pressure, with a friction distance of 10 cm being counted as one time. The hydrophobicity of the surface of the solid transparent lubricating coating was tested after each two frictions using an OCA20 contact angle tester to obtain the water contact angle WCA and the rolling angle WSA.

[0050] (5) Test the hydrophobicity of the solid lubricating coating of the sample after rubbing with gauze: The solid lubricating coating of the sample is rubbed with flannel under a 50g weight pressure, with a friction distance of 10cm as one time, for a total of 30 times. The hydrophobicity of the surface of the solid transparent lubricating coating is tested after every two frictions using an OCA20 contact angle tester to obtain the water contact angle WCA and the rolling angle WSA.

[0051] Embodiment 1:

[0052] A preferred embodiment of the method for preparing the fluorine-free transparent self-cleaning solid lubricating coating of the present invention comprises the following steps:

[0053] S1. Preparation of wax micropowder:

[0054] 20g of microcrystalline wax was placed in a 50mL beaker and dissolved by heating in an 80℃ water bath. The dissolved wax was sprayed out through a 0.5mm-diameter spray gun. The spray gun air pressure was provided by a 30L, 980W air pump air compressor. The air pipe connected to the air pump was preheated in advance. The sprayed wax would immediately form a spherical shape in the air and finally collected in a container to obtain wax powder with a particle size of 5 to 20μm.

[0055] S2. Preparation of wax-based suspension:

[0056] The wax micropowder prepared in step S1 is added to 16 g of ethyl acetate solution, wherein the weight concentration of the wax micropowder in the ethyl acetate solution is 0.3 wt %. Then, PDMS and hydrophilic nano-silica are added, wherein the weight concentration of the PDMS in the ethyl acetate solution is 22 wt %, and the weight concentration of the hydrophilic nano-silica in the ethyl acetate solution is 0.5 wt %. Subsequently, magnetic stirring is performed at room temperature for 2 h, ultrasonic dispersion is performed for 1 h, and a wax-based suspension is obtained by uniform dispersion.

[0057] S3. Preparation of solid lubricating coating:

[0058] A glass slide was used as a substrate and soaked in anhydrous ethanol for 10 minutes. The substrate was then taken out and dried at 60°C to obtain a clean substrate. The wax-based suspension described in step S2 was sprayed with a spray gun of model Gunze PS289 at a distance of 10 cm from the clean substrate and perpendicular to the clean substrate at an air pressure of 0.2 MPa to prepare a sample. The sample was then placed in a forced air drying oven at 60°C for drying and curing for 12 hours to obtain a solid lubricating coating.

[0059] In order to investigate the effect of wax powder concentration on the solid lubricating coating, the weight concentration of the wax powder in the ethyl acetate solution in Example 1 was replaced with different wax powder concentrations to prepare coatings. The hydrophobicity, optical transparency and power change after pollution self-cleaning of each coating under the same environment as the commercial coating were tested. The results are shown in Table 1 below:

[0060] Table 1. Solid lubricant coating properties with different wax powder concentrations

[0061]

[0062] By the attached Figure 1 It can be seen that the obtained wax powder exhibits a good spherical morphology. From the comparison results of Examples 1 to 3 with Comparative Examples 1 and 2, it can be seen that the wax powder is used to provide the coating with a certain roughness and hydrophobicity. From the test results of the water contact angle WCA and the rolling angle WSA, it can be seen that the solid lubricating coating has excellent hydrophobicity and lubrication properties. From the transparency results, it can be seen that the solid lubricating coating has good optical transparency. The solid lubricating coating is applied to the surface of the solar panel. The power loss after self-cleaning is significantly reduced compared with the commercial coating. It can be seen that the solid lubricating coating has excellent self-cleaning, hydrophobicity and durability, which is beneficial to reducing the power loss of the photovoltaic panel after self-cleaning after pollution. However, the wax powder is a white powder. In order to further avoid excessive wax powder and loss of optical transparency of the coating, the weight concentration of the wax powder in the solvent is preferably 0.3wt% to 2wt%. Considering the hydrophobicity and transparency of the coating, it can be further preferably 0.6wt% to 1wt%.

[0063] Embodiment 4:

[0064] A preferred embodiment of the method for preparing the fluorine-free transparent self-cleaning solid lubricating coating of the present invention comprises the following steps:

[0065] S1. Preparation of wax micropowder:

[0066] 20g of microcrystalline wax was placed in a 50mL beaker and dissolved by heating in an 80℃ water bath. The dissolved wax was sprayed out through a 0.5mm-diameter spray gun. The spray gun air pressure was provided by a 30L, 980W air pump air compressor. The air pipe connected to the air pump was preheated in advance. The sprayed wax would immediately form a spherical shape in the air and finally collected in a container to obtain wax powder with a particle size of 5 to 20μm.

[0067] S2. Preparation of wax-based suspension:

[0068] The wax micropowder prepared in step S1 is added to 16 g of ethyl acetate solution, wherein the weight concentration of the wax micropowder in the ethyl acetate solution is 0.8 wt %. Then PDMS and hydrophilic nano-silica are added, wherein the weight concentration of the PDMS in the ethyl acetate solution is 5 wt %, and the weight concentration of the hydrophilic nano-silica in the ethyl acetate solution is 0.5 wt %. Subsequently, magnetic stirring is performed at room temperature for 2 h, ultrasonic dispersion is performed for 1 h, and a wax-based suspension is obtained by uniform dispersion.

[0069] S3. Preparation of solid lubricating coating:

[0070] A glass slide was used as a substrate and soaked in anhydrous ethanol for 10 minutes. The substrate was then taken out and dried at 60°C to obtain a clean substrate. The wax-based suspension described in step S2 was sprayed with a spray gun of model Gunze PS289 at a distance of 10 cm from the clean substrate and perpendicular to the clean substrate at an air pressure of 0.2 MPa to prepare a sample. The sample was then placed in a forced air drying oven at 60°C for drying and curing for 12 hours to obtain a solid lubricating coating.

[0071] In order to investigate the effect of PDMS concentration on the solid lubricating coating, the weight concentration of PDMS in the ethyl acetate solution in Example 4 was replaced with different wax powder concentrations to prepare coatings. The hydrophobicity, optical transparency and power change after pollution self-cleaning of each coating under the same environment as the commercial coating were tested. The results are shown in Table 2 below:

[0072] Table 2. Properties of solid lubricant coatings with different PDMS concentrations

[0073]

[0074] From the comparison results of Examples 4 to 6 with Comparative Examples 3 and 4, it can be seen that the role of PDMS is to provide hydrophobicity and also act as an adhesive in the coating. PDMS itself has high transparency and will not affect the transparency of the coating. From the test results of the water contact angle WCA and the rolling angle WSA, it can be seen that the solid lubricating coating has excellent hydrophobicity and lubrication properties. From the transparency results, it can be seen that the solid lubricating coating has good optical transparency. The solid lubricating coating is applied to the surface of the solar panel, and the power loss after self-cleaning is significantly reduced compared with the commercial coating. It can be seen that the solid lubricating coating has excellent self-cleaning, hydrophobicity and durability, which is beneficial to reducing the power loss of the photovoltaic panel after self-cleaning after pollution. However, in order to further avoid excessive PDMS and be unfavorable to smooth spraying or batch production, the weight concentration of the PDMS in the solvent is preferably 5wt% to 40wt%, and considering the hydrophobicity and transparency of the coating, it can be further preferably 20wt% to 30wt%.

[0075] Embodiment 7:

[0076] A preferred embodiment of the method for preparing the fluorine-free transparent self-cleaning solid lubricating coating of the present invention comprises the following steps:

[0077] S1. Preparation of wax micropowder:

[0078] 20g of microcrystalline wax was placed in a 50mL beaker and dissolved by heating in an 80℃ water bath. The dissolved wax was sprayed out through a 0.5mm-diameter spray gun. The spray gun air pressure was provided by a 30L, 980W air pump air compressor. The air pipe connected to the air pump was preheated in advance. The sprayed wax would immediately form a spherical shape in the air and finally collected in a container to obtain wax powder with a particle size of 5 to 20μm.

[0079] S2. Preparation of wax-based suspension:

[0080] The wax micropowder prepared in step S1 is added to 16 g of ethyl acetate solution, wherein the weight concentration of the wax micropowder in the ethyl acetate solution is 0.8 wt %. Then PDMS and hydrophilic nano-silica are added, wherein the weight concentration of the PDMS in the ethyl acetate solution is 25 wt %, and the weight concentration of the hydrophilic nano-silica in the ethyl acetate solution is 0.3 wt %. Subsequently, magnetic stirring is performed at room temperature for 2 h, ultrasonic dispersion is performed for 1 h, and a wax-based suspension is obtained by uniform dispersion.

[0081] S3. Preparation of solid lubricating coating:

[0082] A glass slide was used as a substrate and soaked in anhydrous ethanol for 10 minutes. The substrate was then taken out and dried at 60°C to obtain a clean substrate. The wax-based suspension described in step S2 was sprayed with a spray gun of model Gunze PS289 at a distance of 10 cm from the clean substrate and perpendicular to the clean substrate at an air pressure of 0.2 MPa to prepare a sample. The sample was then placed in a forced air drying oven at 60°C for drying and curing for 12 hours to obtain a solid lubricating coating.

[0083] In order to investigate the effect of hydrophilic nano-silica concentration on the solid lubricating coating, the weight concentration of hydrophilic nano-silica in the ethyl acetate solution in Example 7 was replaced with different wax powder concentrations to prepare coatings. The hydrophobicity, optical transparency and power change after pollution self-cleaning of each coating under the same environment as the commercial coating were tested. The results are shown in Table 3 below:

[0084] Table 3. Properties of solid lubricating coatings with different hydrophilic nano-silica concentrations

[0085]

[0086]

[0087] From the comparison results of Examples 7 to 9 with Comparative Examples 5 and 6, it can be seen that hydrophilic nano-silicon dioxide can increase the hardness of the coating and a certain water contact angle. Figure 2 The test results of water contact angle WCA and rolling angle WSA show that the solid lubricating coating has excellent hydrophobicity and lubrication properties. Figure 3, Attachment Figure 4 The results of the optical transparency show that the solid lubricating coating has good optical transparency at different wavelengths. The solid lubricating coating is applied to the surface of the solar panel, and the power loss after self-cleaning is significantly reduced compared with the commercial coating. It can be seen that the solid lubricating coating has excellent self-cleaning, hydrophobicity and durability, which is beneficial to reduce the power loss of the photovoltaic panel after self-cleaning after pollution, and can ensure the power generation efficiency of the solar photovoltaic panel for a long time. However, in order to further avoid the loss of hydrophobicity and optical transparency of the coating due to excessive hydrophilic nano-silica, the weight concentration of the hydrophilic nano-silica in the solvent is preferably 0.3wt% to 1wt%. Taking into account the hydrophobicity and transparency of the coating, it may be further preferably 0.5wt% to 0.7wt%.

[0088] By the attached Figure 5 and attached Figure 6 It can be seen that the solid lubricating coating obtained by the present invention can still maintain hydrophobic properties after being rubbed with sandpaper and gauze, and has excellent hydrophobicity and stability. It can be seen from the results of Examples 1 to 9 that the solid lubricating coating obtained by the present invention has good optical transparency, excellent self-cleaning, hydrophobicity, stability and durability. The preparation method is simple and environmentally friendly, and there is no fluorine and no VOC emissions. A solid lubricating coating with high transparency is obtained using environmentally friendly wax, so that it can be used in multiple fields such as solar panels, building exterior walls, and automobile surfaces, and has broad commercial application prospects.

[0089] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention, and they are not intended to limit the scope of protection of the present invention. For example, the substrate material can be selected as needed and is not limited to glass slides. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.

Claims

1. A fluorine-free transparent self-cleaning solid lubricating coating, characterized in that: The solid lubricating coating is formed by coating a wax-based suspension on a substrate and solidifying the wax-based suspension, wherein the wax-based suspension is prepared by dispersing wax micropowder, a hydrophobic adhesive and hydrophilic nano-silicon dioxide in a solvent.

2. The fluorine-free transparent self-cleaning solid lubricating coating according to claim 1, characterized in that: The particle size of the wax powder is 5 to 20 μm, and the weight concentration of the wax powder in the solvent is 0.3 wt % to 2 wt %.

3. The fluorine-free transparent self-cleaning solid lubricating coating according to claim 1, characterized in that: The hydrophobic adhesive is PDMS, and the weight concentration of the PDMS in the solvent is 5wt% to 40wt%.

4. The fluorine-free transparent self-cleaning solid lubricating coating according to claim 1, characterized in that: The weight concentration of the hydrophilic nano-silicon dioxide in the solvent is 0.3 wt % to 1 wt %.

5. The fluorine-free transparent self-cleaning solid lubricating coating according to claim 1, characterized in that: The solvent is ethyl acetate solution.

6. The method for preparing a fluorine-free transparent self-cleaning solid lubricating coating according to any one of claims 1 to 5, characterized in that: The preparation method thereof comprises: Preparation of wax-based suspension: adding wax micropowder to a solvent, and then adding a hydrophobic adhesive and hydrophilic nano-silica to disperse uniformly to prepare a wax-based suspension; Preparation of self-cleaning lubricating coating: spraying the wax-based suspension onto the surface of a substrate and curing the wax-based suspension to obtain a self-cleaning lubricating coating.

7. The method for preparing the fluorine-free transparent self-cleaning solid lubricating coating according to claim 6, characterized in that: The preparation method thereof comprises: Preparation of wax micropowder: Heat and dissolve the microcrystalline wax, spray it out through a spray gun, and collect it to form spherical wax micropowder.

8. The method for preparing the fluorine-free transparent self-cleaning solid lubricating coating according to claim 6, characterized in that: Magnetic stirring and ultrasonic dispersion are used to prepare the wax-based suspension.

9. The method for preparing the fluorine-free transparent self-cleaning solid lubricating coating according to claim 6, characterized in that: When preparing the self-cleaning lubricating coating, the substrate surface is cleaned with anhydrous ethanol before spraying, and air-dried and cured.

10. The use of the fluorine-free transparent self-cleaning solid lubricating coating according to any one of claims 1 to 5, characterized in that: The invention comprises using the solid lubricating coating for solar panels, building exterior walls and automobile surfaces.

Citation Information

Patent Citations

  • Surface-treated powder and cosmetic comprising the same

    CN102036650A

  • Super-hydrophobic self-cleaning composite paint, preparation method of super-hydrophobic self-cleaning composite paint and self-cleaning insulator using super-hydrophobic self-cleaning composite paint

    CN108250946A

  • Preparation method of self-repairing microcapsules and application thereof in super-hydrophobic coating

    CN110449094A

  • Concrete waterproofing agent and application thereof

    CN113636862A

  • Coatings for marine vessels that reduce cavitation

    WO2022256945A1

Cited By

  • Fluorine-free heat-resistant solid super-hydrophobic coating and preparation method thereof

    CN120442162A